2003
DOI: 10.3168/jds.s0022-0302(03)73671-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Intensity During the Dry Period. 2. Metabolic and Hormonal Responses

Abstract: The metabolic response to different feeding levels during the dry period was studied in 24 multiparous dairy cows of the Swedish Red and White breed. The cows represented two lines, selected for high or low milk fat percentage, at the same amount of energy produced in milk. The cows were fed one of three different amounts of the same total mixed diet during the dry period, starting 8 wk prior to the expected parturition. The rations provided 71, 106, or 177 MJ metabolizable energy per day. After parturition th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
211
3
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(279 citation statements)
references
References 29 publications
55
211
3
10
Order By: Relevance
“…The higher glucose and lower NEFA concentrations during the last 3 weeks of gestation (Table 2) in cows offered the H diet suggest that these cows were mobilising less body fat than cows offered diet L, which was attributable to the differences in energy intake. A similar effect has also been observed during the last few weeks of gestation in other experiments (Grum et al, 1996;Holtenius et al, 2003;Rabelo et al, 2005;Douglas et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The higher glucose and lower NEFA concentrations during the last 3 weeks of gestation (Table 2) in cows offered the H diet suggest that these cows were mobilising less body fat than cows offered diet L, which was attributable to the differences in energy intake. A similar effect has also been observed during the last few weeks of gestation in other experiments (Grum et al, 1996;Holtenius et al, 2003;Rabelo et al, 2005;Douglas et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Post-calving blood concentrations of NEFA also indicated that cows on treatment HL mobilised more body reserves than cows on the other treatments. The higher NEFA concentrations, post-calving, in cows offered diet H pre-calving were most likely because of the higher BCS of these cows at calving and thus their tendency to mobilise more in the first weeks of lactation ( Figure 2); this is in accordance with other studies where a difference in BCS was obtained during the last part of gestation Holtenius et al, 2003). The higher BHB level and lower glucose level post-calving in cows on treatment HL was probably a consequence of their higher NEFA level that was partly oxidised to ketone bodies in the liver.…”
Section: Effect Of Diet On Post-calving Measuressupporting
confidence: 91%
See 2 more Smart Citations
“…As previously found by Holtenius and Holtenius (2007), plasma components vary over the periods but not the RQUICKI index, so it seems a good indicator to identify changes in insulin sensitivity for these cows. Moreover, we found a correlation between BCS and RQUICKI, in accordance with Holtenius et al (2003) suggesting that cows with high BCS should have a lower RQUICKI and be more insulin resistant than the thin cows (Holtenius et al, 2003). Our RQUICKI values were not affected by the period of the lactation.…”
Section: Discussionsupporting
confidence: 78%